Improving Digital Sales and Marketing Recording Capabilities for UMKM Carving Craftsmen in Sumita Village, Gianyar Regency, Bali Province - PRILIANDANI, Ni Made Intan; TRISNADEWI, A.A Ayu Erna; SUMARTINI, Ade Ruly (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Kuliah Kerja Nyata (KKN) is an extracurricular activity and community service program that students carry out. This program is typically part of the university curriculum and is required to complete an undergraduate degree. Sumita Village is one of the villages that has established a partnership with Warmadewa University. During the KKN, students identified several issues SMEs (Small and medium enterprises) faced regarding carving artisans in Sumita Village. The main problem in Sumita Village is adequate sales record-keeping among the carving artisans and their limited understanding of digital sales concepts. These issues have prevented the artisans in Sumita Village from expanding their sales to reach a broader market. Based on these findings, the KKN activities in Sumita Village designed a program to provide training on sales record-keeping and online sales. After implementing this program, the impact on the community included an increased understanding of the importance of sales record-keeping among the partners, who have also been able to create simple sales records. Additionally, the partners understood the concept of online sales, enabling them to apply this system to expand their market reach.